2021
DOI: 10.32047/cwb.2021.26.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanical properties and durability indices of concrete containing Fe3O4/SiO2/GO and GO nanoparticles

Abstract: Recent research in the construction industry justifi es the partial replacement of cement by nanomaterials. Graphene oxide na-nocomposite is a material that has been recently proposed as a suitable alternative for part of cement in concrete. However, there is no research on the addition of these synthetic compounds to concrete, and little is known about the effect of these materials on the mechanical and durability properties of concrete. Therefore, in this laboratory study, the synthesis of Fe3O4/SiO2/GO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Nanocząstki wprowadzone do betonu zmniejszają jego gęstość oraz rozmiar porów. Właściwości można w dużym stopniu poprawić przez reakcję między nanocząstkami a produktami hydratacji, zgodnie z (6)(7)(8)(9). Dodanie niewielkiej ilości nanocząstek do betonu znacznie zwiększa jego wytrzymałość i trwałość.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Nanocząstki wprowadzone do betonu zmniejszają jego gęstość oraz rozmiar porów. Właściwości można w dużym stopniu poprawić przez reakcję między nanocząstkami a produktami hydratacji, zgodnie z (6)(7)(8)(9). Dodanie niewielkiej ilości nanocząstek do betonu znacznie zwiększa jego wytrzymałość i trwałość.…”
Section: Introductionunclassified
“…Nanoparticles reduce the density and pore size of concrete when incorporated into the material. A great deal of performance can be improved by the reaction between nanoparticles and hydrate products, according to (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles can increase the density of particles in concrete, thereby increasing the density of nanostructures in concrete and improving its mechanical properties. Using nanoparticles to strengthen concrete has been proven [15,16]. In addition to serving as a filler in concrete microstructures, concluded that nanosilica acts as an activator in pozzolanic reactions [17].…”
Section: Introductionmentioning
confidence: 99%